Evaluasi dan Penguatan Organizational Resilience di Perguruan Tinggi Vokasi: Pendekatan Systematic Literature Review (SLR) dalam Menjawab Tantangan Institusional: Penelitian - Nika Sintesa Grinika; Rais Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore and identify factors that strengthen organizational resilience in vocational colleges using the Systematic Literature Review (SLR) approach method based on the PRISMA model. This study was conducted on 25 scientific articles indexed by Scopus for the 2020-2025 period and selected based on relevant topic criteria. Data was collected from Harzing's Publish or Perish (PoP) application taken from Crossref and Google Scholar. The identification process uses keywords such as "Organizational resilience framework, performance strategy and organizational strategy. Based on the analysis of existing literature, organizational resilience in vocational higher education can be strengthened through several key elements, namely responsive and adaptive leadership, application of technology, social intelligence, internal and external cooperation, and organizational culture. This study also suggests that vocational colleges develop proactive, innovation-based, and diversified strategies in the face of rapid change. The contribution of this research is to develop an integrated model of organizational resilience for vocational colleges, which also serves as a strategic guide.